2017
DOI: 10.19044/esj.2017.v13n5p82
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Destination Image and the Intention to Revisit: A Study Regarding Arab Tourists

Abstract: The objective of this study is to determine the impact of destination image (cognitive and affective image) on the intention of Arab tourists to revisit Istanbul. The sample group of the study is comprised of Arab tourists who visited Istanbul in January-April 2016. Data was obtained from a total of 385 Arab tourists for the application. Descriptive analyses such as percentage, frequency as well as statistical tests such as factor analysis (confirmatory), reliability analysis were used in the analysis of the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
2
13

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 30 publications
(5 reference statements)
3
11
2
13
Order By: Relevance
“…In contrast, our findings were not in line with previous studies [113][114][115]. Artuger and Cetinsoz [114] examined the impact of destination image (cognitive image and affective image) on revisiting intention and concluded that affective image positively, but insignificantly, influenced travel intention. Furthermore, they mentioned that previous studies had only considered the cognitive aspect of the destination image, whereas affective image also contains equal importance in an accurate assessment of the influence of destination image in the decision-making process.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast, our findings were not in line with previous studies [113][114][115]. Artuger and Cetinsoz [114] examined the impact of destination image (cognitive image and affective image) on revisiting intention and concluded that affective image positively, but insignificantly, influenced travel intention. Furthermore, they mentioned that previous studies had only considered the cognitive aspect of the destination image, whereas affective image also contains equal importance in an accurate assessment of the influence of destination image in the decision-making process.…”
Section: Discussioncontrasting
confidence: 99%
“…Information given by tourists about the destination image was significant because potential travelers mostly relied on the opinions and advice provided by those users who have experienced the same services [56], and therefore a perceived image of a target location positively and significantly influenced the tourists' attitudes [112]. In contrast, our findings were not in line with previous studies [113][114][115]. Artuger and Cetinsoz [114] examined the impact of destination image (cognitive image and affective image) on revisiting intention and concluded that affective image positively, but insignificantly, influenced travel intention.…”
Section: Discussioncontrasting
confidence: 94%
“…Gallarza, Gil Saura ve Garcia (2002) destinayon imajı ile ilgili literatüre ilk kapsamlı katkıyı sağlamışlar ve destinasyon imajını karmaşık, çok boyutlu ve dinamik bir kavram olarak tanımlamışlardır. Birçok araştırmacı destinasyon imajını ölçmeye çalışmış ancak ölçümlerin geçerliliği ve güvenilirliği nedeniyle başarısız olurken bu konuda çok az sayıda araştırmacı başarılı olmuştur (Artuğer ve Çetinsöz, 2017).…”
Section: Desti̇nasyon İmaji Ve Desti̇nasyon Ki̇şi̇li̇ği̇unclassified
“…Those who have investigated RVIs studied mainly travel motivations and satisfaction from previous visits [Kozak and Rimmington, 2000;Bigne et al, 2001;Bowen, 2001;Kozak, 2001;Um et al, 2006;Huang and Hsu, 2009;Ramseook-Munhurrun et al, 2015]. As was already mentioned, the overwhelming majority of authors explored loyalty intentions or loyalty behavior in the context of specific, explicitly defined destinations, which lowered validity of any general conclusions about drivers of loyalty [George and George, 2004;Yoon and Uysal, 2005;Chen and Tsai, 2007;Kim and Brown, 2012;Assaker and Hallak, 2013;Artuger and Cetinsoz, 2017] and on Polish tourist market [Seweryn, 2010]. The current study, by measuring overall loyalty intentions separately from any particular place, attempts to provide insights into general loyalty forming patterns.…”
Section: Literature Review and Hypotheses 21 Research Gap Identificamentioning
confidence: 99%